Long-gap esophageal atresia: management, most frequent complications, and expert recommendations – review of literature - Kędzierska, Zofia; Dadas, Klaudia; Żurek, Urszula; Tołwiński, Ignacy; Świercz, Aleksandra; Małachowska, Dominika; Ciecierski-Koźlarek, Hubert; Antkowiak, Klaudia; Shved, Kateryna (Journal of Education, Health and Sport, 2023)
Introduction and aim of the study. Long-gap esophageal atresia (LGEA) is a congenital anomaly in which the gap between both ends of the esophagus exceeds three intervertebral spaces and is an esophageal atresia without air in the abdomen. The defect is both therapeutic and surgical challenge. This review aims at providing an overview of the most recent literature on the effective methods for treatment of LGEA, and the most frequent complications and experts’ recommendations on this subject. Material and methods. The systematic review was based on available data collected using PubMed database and the Google Scholar web search engine. Analysis of the literature. There is no consensus on the ideal technique for surgical treatment of LGEA. There are two possible approaches for opening the thorax – thoracotomy and thoracoscopy. The techniques stimulating esophageal elongation include external and internal traction techniques, magnetic compression anastomosis and intramural botulinum type A toxin injection. Replacement methods are a viable option when it is impossible to preserve the native esophagus. Decellularized matrices seem to be promising in developing an esophageal substitute. Regardless of the surgical approach a common complication of surgical treatment is anastomotic stenosis which requires further surgical interventions. Conclusion. Elongation techniques are effective in approximation of the proximal and distal esophagus. The future lies with tissue engineering and inventing an off-the-shelf esophageal substitute. The centralization of treatment is recommended. After discharge from hospital interdisciplinary outpatient assessment and care is required. Further prospective studies are needed to determine the optimal mode of treatment and prevent complications associated with LGEA.